Vote buying or (political) business (cycles) as usual? - Toke Aidt; Zareh Asatryan; Lusine Badalyan; Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
We provide new evidence on the short-run effect of elections on monetary aggregates. We study month-to-month fluctuations in the growth rate of M1 in a sample of 85 low and middle income democracies from 1975 to 2009. The evidence shows an increase in the growth rate of M1 during election months of about one tenth of a standard deviation. A similar effect can neither be detected in established OECD democracies nor in the months leading up to the election. The effect is larger in democracies with many poor and uneducated voters, and in Sub-Saharan Africa and in East-Asia and the Pacific. We show that the election month monetary expansion is demand driven and can be best explained by systemic vote buying. Systemic vote buying requires significant amounts of cash to be disbursed right before elections. The finely timed increase in M1 that we observe in the data is consistent with this. The timing is inconsistent with a monetary cycle aimed at creating an election time boom and it cannot be, fully, accounted for by other possible explanations.
urn:nbn:de:bsz:180-madoc-388239
Keywords: D72; E51; O10; 330; political business cycles; vote buying; monetary economics